RASIO LEBAR DAN TINGGI BALOK TERHADAP KUAT LENTUR - Andi Marini Indriani; Agus Sugianto (Universitas Lambung Mangkurat, 2016)
Behavior and flexural strength of reinforced concrete with medium concentration is influenced by several factors such as the dimensions, shape the beam section, the number and arrangement of reinforcement bending, compression reinforcement, stretch ratio (a/d) and the properties of concrete and steel.The construction perpetrators must understand the impact of the ratio b/h against a concrete beam flexural strength and deformation so that the construction can obtain optimal results. The methodology used in this research is the creation of concrete beams with varying ratios b / h The ratio b / h is 1; 1.25and 1.5. Using concrete (fc ') 26.73 Mpa, plain steel 6 mm diameter is used for begel, diameter 8 is used to reinforce the attraction and a diameter of 10 are used as reinforcement press.The results show that changes in beam width ratio> 1.25 specimens apparently can not bear the burden of making that happen more dominant withstand tensile reinforcement. And from a comparison test with a ratio of 1: 1.25: 1.5 was the optimal ratio of the bending beam is 1.25.